1988
DOI: 10.1093/carcin/9.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gap junctional blockage by palmitoyl carnitine and TMB-8 in a rat liver epithelial cell line

Abstract: Exposure to 12-O-tetradecanoylphorbol-13-acetate (TPA) has been shown to inhibit gap junctional intercellular communication (GJIC) in many cell types in vitro. Using a scrape loading/dye transfer technique, TPA was shown to cause a dose-dependent and transient inhibition of GJIC in WB-F344, a normal rat liver epithelial cell line. Such a down-modulation of intercellular communication was found to be associated with an increase in protein kinase C (PKC) activity. Translocation of this activity to the particulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…agonists initiate their effects on communication through different receptor systems that are down-regulated by the specific ligand. In the case of PMA, the receptor is likely to be the protein kinase C family of proteins, and preincubation of WB cells with the phorbol ester for 6 h has been shown to cause a marked loss of Ca2+-and phospholipid-dependent kinase activity [21]. Separate experiments established that pretreatment of WB cells with PMA blocked the capacity of the phorbol ester to inhibit dye transfer, but did not decrease the inhibitory effect of LPA (Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…agonists initiate their effects on communication through different receptor systems that are down-regulated by the specific ligand. In the case of PMA, the receptor is likely to be the protein kinase C family of proteins, and preincubation of WB cells with the phorbol ester for 6 h has been shown to cause a marked loss of Ca2+-and phospholipid-dependent kinase activity [21]. Separate experiments established that pretreatment of WB cells with PMA blocked the capacity of the phorbol ester to inhibit dye transfer, but did not decrease the inhibitory effect of LPA (Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…The first concern is that the scraped cells do not uniformly label with Lucifer yellow, regardless of the presence or absence of chemical treatment. Other studies have published photographs illustrating similarly inconsistent labeling patterns (E1-Fouly et al, 1987;Kavanagh et al, 1987;Suter et al, 1987;Oh et al, 1988;Nicholson et al, 1988;Evans et al, 1988aEvans et al, , 1988bMadhukar et al, 1989;Loch-Caruso et al, 1990), and a representative example from our laboratory is shown in Figure 2. Several factors may contribute to this lack of uniform dye labeling.…”
Section: Discussionmentioning
confidence: 57%
“…The SL/DT assay has been used traditionally as a screening tool to evaluate the qualitative effects of chemicals on GJIC. However, more recently, the SL/DT assay has been used to obtain quantitative concentration-dependent responses of chemically induced inhibition (Surer et al, 1987;Evans et al, 1988aEvans et al, , 1988bOh et al, 1988;LochCaruso, 1990). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gap junctions provide cells with intracellular conduits for communication and transfer of essential metabolites and ions. Most tumor promoting agents, such as 12-O-tetradecanoylphorbol-13-acetate (TPA), can inhibit intercellular communications in cultured cells [Oh et al, 1988;Gao et al, 1992;Nielson et al, 2000], and reduced or dysfunctional GJIC capacity has been associated with carcinogenesis [Yamasaki, 1996].…”
Section: Introductionmentioning
confidence: 99%